Geomorphology of Mount Ararat/Ağri Daği (Ağri Daği Milli Parki, Eastern Anatolia, Turkey) - R.S. Azzoni; A. Zerboni; M. Pelfini; C. Smiraglia; G. A. Diolaiuti; C. A. Garzonio; R. Cioni; E. Meraldi (Journal of Maps, 2017)
This paper presents a geomorphological map of Mount Ararat/Ağri Daği in Eastern Anatolia (Turkey). Mount Ararat/Ağri Daği is a volcanic complex covered by a unique ice cap in the Near East. The massif is the result of multiple volcanic phases, and present day landforms are the result of subsequent and overlapping glacial, periglacial, and slope processes. The geomorphological mapping of Mount Ararat/Ağri Daği was firstly performed on the basis of desktop studies, by applying remote-sensing investigations using high-resolution satellite imagery (PLEIADES and SPOT images). A preliminary draft of the map was crosschecked and validated in the field as part of an interdisciplinary campaign carried out in the 2014 summer season. All the collected data suggest that the Mount Ararat/Ağri Daği glaciation played a crucial role in the evolution of the landscape and that even today glaciers are significant features in this area. Currently, ice bodies cover 7.28 km2 and include peculiar glacier types. Among these are three well-developed debris-covered glaciers, flowing down along the flanks of the volcano.